Multi-shell structure material with metal element concentration gradient as well as preparation method and application of multi-shell structure material
By using the sequence template method and a two-step roasting strategy to construct a hollow multi-shell structural material with a metal element concentration gradient, the performance decay problem of nickel-rich ternary positive electrode material in lithium-ion batteries is solved, and the energy density, cycle stability and rate performance of the battery is improved.
Patent Information
- Application Number
- CN202411878753.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing nickel-rich ternary cathode materials have problems such as cation mixing, transition metal dissolution, active Li loss and surface reconstruction in lithium-ion batteries, resulting in rapid decline in battery performance and limiting their practical application.
The order template method and a two-step metal ion precursor enrichment strategy combined with a two-step calcination strategy were used to construct a hollow multi-shell structural material with a metal element concentration gradient. By regulating the synthesis conditions, the controllable synthesis of the composition, structure and morphology of the material is achieved, and the problem of structural collapse during the charging and discharging process is overcome.
The energy density, cycle stability and rate performance of the cathode material of lithium-ion batteries has been comprehensively improved, extending the cycle life of the battery and improving stability.
Smart Images

Figure CN119683700A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional materials, and in particular to a multi-shell structure material with a metal element concentration gradient, a preparation method and an application thereof. Background Art
[0002] The performance of lithium-ion batteries mainly depends on the electrode materials. Among them, the research on negative electrode materials has made continuous breakthroughs in performance since the initial commercial graphite (374mAh / g) to the discovery of silicon, tin, lithium, etc. At present, the specific capacity of positive electrode materials is much lower than that of negative electrode materials. Therefore, positive electrode materials have become a shortcoming restricting the development of lithium-ion batteries. So far, commercial lithium-ion battery positive electrode materials have mainly gone through three stages: LiCoO2 (LCO), LiMn2O4 (LMO) and LiFePO4 (LFP), and LiNi x Co y Mn 1-x-y O2(NCM). The ternary layered oxide NCM developed by Ohzuku's team in 1994 is considered to be the most promising candidate material for high-performance lithium-ion batteries. Among NCM positive electrode materials, nickel is the main provider of capacity, and due to the cost of cobalt resources, research on "nickel-rich" NCM positive electrode materials is becoming increasingly popular. However, "nickel-rich" NCM positive electrode materials face problems such as cation mixing, transition metal dissolution, active Li loss, and surface reconstruction. These problems lead to rapid degradation of battery performance and also bring about problems such as safety performance, which limits its practical application.
[0003] At present, the modification measures of "nickel-rich" NCM positive electrode materials include ion doping, surface coating, special structural design, and construction of element concentration gradients. The design of constructing element concentration gradients is favored by researchers because it does not introduce electrochemically inert elements and has low cost, but the current construction of concentration gradients is still technically difficult. At present, the co-precipitation method is generally used to construct nickel-rich positive electrode materials with concentration gradients. Due to the complexity of the process and too many influencing factors, the overall element concentration is uncontrollable, and it is impossible to achieve accurate element concentration gradient distribution control. In addition, a single modification measure cannot suppress a variety of potential failure factors. Current research mainly focuses on the parallel use of multiple modification measures. In this context, how to combine multiple modification measures has become a hot spot and difficulty in current research. Summary of the invention
[0004] Based on the above-mentioned deficiencies of the prior art, the present invention provides a hollow multi-shell structure material with a metal element concentration gradient, and a preparation method and application thereof. Based on the sequential template method, the present invention adopts a two-step metal ion precursor enrichment strategy combined with a two-step calcination strategy to construct a hollow multi-shell structure material with a metal element concentration gradient, and by regulating the synthesis conditions, the composition, structure and morphology of the material are controlled. The problem of structural collapse of nickel-rich ternary positive electrode materials during charging and discharging is overcome at different scales, thereby achieving a comprehensive improvement in energy density, cycle stability and rate performance.
[0005] The present invention provides a type of positive electrode material for lithium-ion batteries and its preparation method and application. The present invention adsorbs a carbon ball template in a solution containing specific metal ions, and after adsorption equilibrium, adds a metal salt to the solution to promote the template to adsorb the metal ions again, and controls the distribution of metal ions in the template by adjusting factors such as adsorption time and adsorption temperature, so that the concentration of metal ions distributed inside and outside the template has obvious differences; then the carbon ball template enriched with metal ions is placed in a tubular furnace for roasting, first roasting in an inert atmosphere to fix the distribution position of the metal ions, and then roasting in an air or oxygen atmosphere, removing the template, and obtaining a hollow multi-shell structure material with a metal element concentration gradient. This material has shown excellent electrochemical properties in lithium battery positive electrode applications due to its unique structural advantages.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for preparing a hollow multi-shell structure material having a metal element concentration gradient, that is, a method for preparing a hollow multi-shell structure material in which the metal element concentrations contained in different shells present a gradient distribution, comprising the following steps:
[0008] 1) heating the carbon source aqueous solution, filtering, washing and drying to prepare micro-nano sized colloidal carbon spheres, which are used as carbon sphere templates for subsequent hollow multi-shell metal oxide synthesis;
[0009] 2) dispersing the carbon sphere template obtained in step 1) in a metal salt solution to obtain a suspension, and after a certain period of stirring, heat preservation and adsorption, the metal salt adsorption reaches a dynamic equilibrium;
[0010] 3) adding a specific metal salt to the suspension after adsorption equilibrium in step 2), stirring, heat preservation and adsorption for a certain period of time, filtering and drying to obtain a solid precursor;
[0011] 4) calcining the solid precursor obtained in step 3) under an inert atmosphere to obtain a solid powder with metal ions initially fixed thereon;
[0012] 5) The solid powder obtained in step 4) is calcined in air or oxygen atmosphere to obtain a hollow multi-shell structure material with a metal element concentration gradient.
[0013] In this method, the use of secondary or multiple adsorption strategies to regulate the distribution of different metal ion precursors in the template is the key to synthesizing multi-shell structure materials with a metal element concentration gradient. In addition, the control of the concentration of the metal ion solution, the solution composition and the adsorption time is the key to regulating the composition and structure of the hollow multi-shell structure material with a metal element concentration gradient. Considering that the carbon sphere template has different adsorption capacities for different metal ions, metal salts of different concentration ratios are added to the solvent to ensure that a solid precursor with a certain metal concentration ratio can be obtained. The solvent composition is regulated to enable the carbon sphere template to adsorb as many metal ions as possible, so that more shells can be obtained; the adsorption time is regulated to enable the carbon sphere template to fully adsorb metal ions; it is worth noting that the control of the type, concentration and adsorption time of metal ions in the secondary adsorption process is the key to synthesizing multi-shell structure materials with a metal element concentration gradient. By controlling the type of metal salts and the concentration of metal ions added in the secondary adsorption process, the solid precursor obtained by the first adsorption further adsorbs specific metal ions, and by regulating the adsorption time, the distribution of the secondary adsorbed metal ions in the template is controlled, thereby obtaining a solid precursor with a metal ion concentration gradient distribution.
[0014] In addition, the high-temperature calcination under an inert atmosphere is chosen first to fix the distribution position of the metal ions in the template and avoid the migration of the metal ions during the oxygen calcination to remove the template and synthesize the metal oxide material. In addition, the structural parameters of the hollow multi-shell structure material can be regulated by regulating the calcination atmosphere, calcination temperature and calcination time. Since the nickel element in the nickel-rich positive electrode material is +2, +3 valence, the cobalt element is +3 valence, and the manganese element is +4 valence, it is necessary to synthesize the nickel-rich positive electrode material with a layered structure in an oxidizing atmosphere; in addition, theoretically, the higher the nickel content, the lower the sintering temperature, and too high a calcination temperature can easily destroy the multi-shell structure and only nanoparticles can be obtained, so it is necessary to regulate the calcination temperature to regulate the crystal structure and geometric structure of the material; in addition, the calcination time also has a great influence on the structure of the material. The longer the calcination time, the better the crystallinity of the material. Considering that the multi-shell structure is difficult to maintain at high temperature, it is designed to be kept warm for a long time at a relatively low temperature to obtain a nickel-rich positive electrode material with an ideal layered structure.
[0015] In the step 1) of the present invention, the carbon source aqueous solution is subjected to hydrothermal reaction to prepare micro-nano sized colloidal carbon spheres. Compared with the traditional mechanical ball milling method, the prepared carbon spheres have uniform particle size and controllable size. At the same time, the surface contains a large number of active functional groups, has excellent hydrophilicity and surface reactivity, is more conducive to the adsorption of metal ions, and is a commonly used template for preparing core-shell structure materials.
[0016] The adsorption described in step 2) of the present invention is enhanced adsorption, which means placing the carbon sphere template and the metal salt solution in a beaker for adsorption at a certain water bath temperature, and regulating the pH value of the metal salt solution to enhance the adsorption of metal ions by the carbon sphere template under appropriate temperature and pH conditions, and obtaining a solid precursor enriched in metal ions after a certain period of adsorption.
[0017] The adsorption described in step 3) of the present invention is adjusted adsorption, which means adding the metal salt to the precursor solution again in proportion, adsorbing at a certain water bath temperature, and regulating the adsorption time to adjust the adsorption of metal ions by the carbon sphere template at appropriate temperature and time, and obtaining a solid precursor with a gradient distribution of metal ions from the inside to the outside after a certain period of adsorption.
[0018] The calcination described in step 4) of the present invention is to gradually solidify the metal ions enriched in the carbon sphere template by controlling the calcination atmosphere, insulation time and calcination temperature, so that the metal ions are stably present in the template and avoid migration due to template removal during the subsequent calcination process.
[0019] The calcination described in step 5) of the present invention is to gradually solidify the metal salt adsorbed on the surface of the carbon ball template by controlling the heating rate, the insulation time and the oxygen concentration in the furnace chamber, and to shrink the template carbon ball and oxidize and burn, while slowly removing the carbon ball template to form a multi-shell structured metal oxide.
[0020] Preferably, the heating reaction in step 1) is a hydrothermal reaction, and the temperature of the hydrothermal reaction is 160-220°C, for example, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C or 200°C, more preferably 180-205°C, and even more preferably 180-200°C;
[0021] Preferably, the metal salt in step 2) comprises one or more of lithium chloride, nickel chloride, manganese chloride, cobalt chloride, lithium acetate, lithium acetate dihydrate, nickel acetate, nickel acetate tetrahydrate, manganese acetate tetrahydrate, cobalt acetate, cobalt acetate tetrahydrate, lithium sulfate, lithium sulfate dihydrate, nickel sulfate, nickel sulfate tetrahydrate, manganese sulfate, manganese sulfate tetrahydrate, cobalt sulfate, cobalt sulfate tetrahydrate, lithium nitrate, lithium nitrate dihydrate, nickel nitrate, nickel nitrate tetrahydrate, manganese nitrate, manganese nitrate tetrahydrate and cobalt nitrate, cobalt nitrate tetrahydrate; more preferably, lithium acetate dihydrate, nickel acetate, nickel acetate tetrahydrate, manganese acetate tetrahydrate, cobalt acetate, cobalt acetate tetrahydrate, lithium sulfate, lithium sulfate dihydrate, nickel sulfate, nickel sulfate tetrahydrate, manganese sulfate, manganese sulfate tetrahydrate, cobalt sulfate, cobalt sulfate tetrahydrate; more preferably, lithium acetate dihydrate, nickel acetate tetrahydrate, manganese acetate tetrahydrate, manganese acetate tetrahydrate, cobalt sulfate, cobalt sulfate tetrahydrate.
[0022] The concentration of the metal salt solution is 0.01-5M, for example, 0.01M, 0.1M, 0.2M, 0.5M, 1M, 2M, 3M, 4M or 5M, more preferably 0.01-3M, and even more preferably 0.01-0.1M;
[0023] The solvent of the metal salt solution includes one or more of water, acetone and ethanol, and more preferably water and / or ethanol.
[0024] Preferably, the adsorption in step 2) is adsorption with heat preservation and stirring;
[0025] The adsorption temperature is 20-60°C, for example, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 60°C, more preferably 30-60°C, and even more preferably 40-50°C;
[0026] One adsorption, the adsorption time is 1-48h, more preferably 1-36h, further preferably 12h;
[0027] Preferably, the adsorption in step 3) is secondary heat preservation and stirring adsorption;
[0028] The adsorption temperature is 20-60°C, for example, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 60°C, more preferably 30-60°C, and even more preferably 40-50°C;
[0029] Secondary adsorption, the adsorption time is 0.1-2h, more preferably 0.1-1h, and further preferably 0.1-0.5h;
[0030] Multiple adsorption, the adsorption time is 0.1-2h, more preferably 0.1-1h, further preferably 0.1-0.5h;
[0031] The adsorbed mixed solution is filtered and washed; the mixed solution is washed with one of deionized water, methanol, ethanol and isopropanol or a combination of any two or more thereof; for example, it may be deionized water, methanol, ethanol, isopropanol, a combination of deionized water and methanol, a combination of deionized water and ethanol, a combination of deionized water and isopropanol, or a combination of methanol and ethanol; the washing times are 2-5 times, for example, 2 times, 3 times, 4 times or 5 times, and more preferably 3-4 times; the washing time is 0.5-24h, for example, 2h, 4h, 6h, 8h, 10h, 11h, 14h, 16h, 18h, 20h, 22h or 24h, more preferably 5-20h, and even more preferably 10-15h;
[0032] The drying temperature is 50-100°C, for example, 50°C, 60°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, more preferably 50-90°C, and even more preferably 60-80°C.
[0033] The drying time is 6-24 h, for example, it can be 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h or 24 h, more preferably 15-24 h, and further preferably 18-20 h.
[0034] Preferably, the calcination in step 4) is carried out in a muffle furnace, a tube furnace or a kiln;
[0035] The calcination temperature is 200-800°C, for example, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, more preferably 300-550°C, and even more preferably 400-500°C;
[0036] The calcination time is 0.5-10 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h or 10 h, more preferably 1-6 h, and further preferably 4-5 h;
[0037] The heating rate of calcination is 0.5-20°C / min, for example, 0.5°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min, 6°C / min, 6.5°C / min, 7°C / min, 7.5°C / min, 8°C / min, 8.5°C / min, 9°C / min, 9.5°C / min or 10°C / min, more preferably 0.5-10°C / min, and further preferably 1-5°C / min;
[0038] The calcination atmosphere is argon or nitrogen, preferably argon, and the purity of high-purity argon is 99.999%.
[0039] Preferably, the calcination in step 5) is carried out in a muffle furnace, a tubular furnace or a kiln;
[0040] The first step calcination temperature is 300-500°C, for example, 300°C, 350°C, 400°C, 450°C and 500°C, more preferably 350-450°C;
[0041] The first step of calcination time is 1-10 hours, for example, it can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, more preferably 5-10h;
[0042] The heating rate of the first step of calcination is 0.5-10°C / min, for example, it can be 0.5°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min, 6°C / min, 6.5°C / min, 7°C / min, 7.5°C / min, 8°C / min, 8.5°C / min, 9°C / min, 9.5°C / min or 10°C / min, more preferably 5-10°C / min;
[0043] The second step calcination temperature is 500-1000°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C and 1000°C, more preferably 500-950°C, and even more preferably 600-800°C.
[0044] The second step calcination time is 15-30h, for example, it can be 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h or 30h, more preferably 15-25h, and further preferably 18-22h;
[0045] The heating rate of the second step calcination is 0.5-20°C / min, for example, 0.5°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min, 6°C / min, 6.5°C / min, 7°C / min, 7.5°C / min, 8°C / min, 8.5°C / min, 9°C / min, 9.5°C / min or 10°C / min, more preferably 0.5-10°C / min, and further preferably 1-5°C / min;
[0046] The calcination atmosphere is one of air, oxygen, or a mixture of nitrogen and oxygen, wherein the proportion of oxygen in the mixture of nitrogen and oxygen is 10%-100%; more preferably, high-purity oxygen.
[0047] The present invention provides a multi-shell structure material with a metal element concentration gradient synthesized by the preparation method. The prepared material not only has a multi-shell structure, but also has different metal element concentrations in different shells, showing a gradient distribution, typically characterized by a high nickel concentration in the inner shell and a low nickel concentration in the outer shell. The multi-shell structure has 2 to 4 shells, for example, 2, 3 or 4 layers.
[0048] The present invention adopts a secondary / multiple adsorption strategy to regulate the conditions of the carbon ball template adsorbing metal ion precursors, such as the concentration of the metal salt precursor solution, the adsorption time, the adsorption temperature, the number of adsorptions and the order, and combines the secondary / multiple roasting strategy, that is, first roasting in an inert atmosphere to fix the distribution position of the metal ions, and then roasting in an oxidizing atmosphere to remove the template, and combined with the regulation of the roasting temperature, the holding time, the heating rate, etc., to prepare a hollow multi-shell structure material with a metal element concentration gradient. Material size nano-sizing can alleviate the powdering phenomenon caused by volume change during the cycle. The multi-shell layer can not only effectively buffer the volume expansion during the charge and discharge process, thereby improving the cycle stability of the material, but also form an effective conductive network inside the material, shorten the transmission path of electrons and lithium ions, thereby improving the rate performance of the material. In addition, the higher concentration of nickel content in the inner shell can provide a high specific capacity for the material, while the lower concentration of nickel content in the outer shell can reduce the dissolution of transition metals, improve the stability of the solid-liquid interface, reduce surface side reactions, and reduce cation mixing, thereby stabilizing the overall structure of the material.
[0049] The hollow multi-shell structure material with a metal element concentration gradient for a lithium-ion battery positive electrode can maintain a specific capacity of 190 mAh / g after more than 100 cycles at a rate of 0.3C in a voltage range of 2.5-4.3 V.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] When the hollow multi-shell structure material with a metal element concentration gradient prepared by the present invention is applied to the positive electrode of a lithium-ion battery, it exhibits excellent cycle stability during high-rate charge and discharge. The nano-sizing of the material can alleviate the pulverization phenomenon caused by volume expansion during the cycle, and the multi-shell structure can not only effectively buffer the volume expansion during the charge and discharge process, ensuring the cycle stability of the material; it can also form an effective conductive network inside the material, which is conducive to the transmission of internal electrons and lithium ions. In addition, due to the unique multi-shell structure nickel concentration gradient distribution of the multi-shell structure material with a metal element concentration gradient, the migration of transition metals is greatly reduced compared with the solid structure gradient material, so that the electrode material has better stability. The nickel concentration gradient distribution, that is, the nickel content of the inner shell is higher, so that the material as a whole has a higher specific capacity, and the nickel content of the outer shell is lower, so that the material has an excellent solid-liquid interface and structural stability, so that the material as a whole has excellent stability. Therefore, the hollow multi-shell structure material with a metal element concentration gradient can maintain a specific capacity of 190 mAh / g after stable cycling at a rate of 0.3C for more than 100 cycles in the voltage range of 2.5-4.3 V, and the capacity retention rate is as high as 98%. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a transmission electron microscope bright field image of the material prepared in Example 1 of the present invention;
[0053] Figure 2 This is a transmission electron microscope bright field image of the material prepared in Example 1 of the present invention after embedding and sectioning;
[0054] Figure 3 The transmission electron microscope-energy dispersive X-ray spectrum line scan of the material prepared in Example 1 of the present invention, the relative content of Ni element in different shell layers (embedded inside is the transmission electron microscope photo of the material);
[0055] Figure 4 This is the X-ray diffraction pattern of the material prepared in Example 1 of the present invention;
[0056] Figure 5 This is the X-ray photoelectron spectroscopy test spectrum of the material prepared in Example 1 of the present invention;
[0057] Figure 6 This is the battery cycle performance curve of the material prepared in Example 1 of the present invention;
[0058] Figure 7 This is the differential scanning calorimetry test result of the material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0059] The present invention is further described in detail below with specific implementation modes.
[0060] The present invention provides a method for preparing a hollow multi-shell structure material having a metal element concentration gradient, the method comprising:
[0061] (a) placing a carbon source aqueous solution into a hydrothermal reactor and performing a hydrothermal reaction at 160-220° C. for 100-180 min, followed by suction filtration, washing, and drying to obtain a carbon sphere template;
[0062] (b) dispersing the carbon sphere template obtained in step (a) in a metal salt solution with a concentration of 0.01-5M to obtain a suspension. The metal salt solution is one or more of lithium chloride, nickel chloride, manganese chloride, cobalt chloride, lithium acetate, nickel acetate, manganese acetate, cobalt acetate, lithium sulfate, nickel sulfate, manganese sulfate, cobalt sulfate, lithium nitrate, nickel nitrate, manganese nitrate, and cobalt nitrate, and adsorbing for 1-48 hours at 20-60°C for a period of time to obtain a suspension;
[0063] (c) adding a metal salt with a concentration of 0.01-5M to the suspension obtained in step (b) again to obtain a suspension. The metal salt is one or more of lithium chloride, nickel chloride, manganese chloride, cobalt chloride, lithium acetate, nickel acetate, manganese acetate, cobalt acetate, lithium sulfate, nickel sulfate, manganese sulfate, cobalt sulfate, lithium nitrate, nickel nitrate, manganese nitrate, and cobalt nitrate, adsorbing at 20-60°C for 0.1-2h, filtering the adsorbed mixed solution, washing with deionized water, methanol or ethanol for 2-5 times, and drying at 60-100°C for 6-24h to obtain a solid precursor; or, repeating the adsorption, filtration, and drying process again to obtain a solid precursor after multiple adsorptions;
[0064] (d) placing the solid precursor obtained in step (c) in a muffle furnace or kiln in an argon or nitrogen atmosphere for 0.5-10 hours at a calcination temperature of 200-800° C. at a heating rate of 0.5-20° C. / min, and obtaining a solid powder after cooling;
[0065] (e) placing the solid powder obtained in step (c) in a muffle furnace or a kiln in air, oxygen, or a mixture of nitrogen and oxygen, wherein the proportion of oxygen in the mixture of nitrogen and oxygen is 10%-100%, and the roasting comprises a two-step roasting process, wherein the first step is a roasting temperature of 300-500°C, a roasting time of 1-10h, and a roasting heating rate of 0.5-10°C / min, and the second step is a roasting temperature of 500-1000°C, a roasting time of 15-30h, and a roasting heating rate of 0.5-20°C / min, and after cooling, the hollow multi-shell structure material with a metal element concentration gradient is obtained.
[0066] Example 1
[0067] A method for preparing a hollow multi-shell structure material having a metal element concentration gradient, the method comprising:
[0068] (1) A 1.5 M sucrose aqueous solution was placed in a reactor at 200° C. for hydrothermal reaction for 127 min. After natural cooling, the mixture was filtered and washed with water 3 times and ethanol 3 times. The product was placed in an oven at 60° C. and dried for 24 h to obtain a carbon sphere template with a diameter of 2.9 μm.
[0069] (2) Grind 1 g of the carbon sphere template obtained in step (1) and add it to a metal salt solution in a molar ratio of 100:10:1:1, i.e., 2 M lithium acetate solution, 0.2 M nickel acetate solution, 0.02 M manganese acetate solution and 0.02 M cobalt acetate, and the solvent is a mixture of 30 ml of deionized water and 20 ml of anhydrous ethanol, stir for 10 min, and then ultrasonicate for 10 min. After the ultrasonication is completed, stir and adsorb at 40° C. for 48 h;
[0070] (3) Add 0.04M cobalt acetate and 0.16M manganese acetate to the solution obtained in (2), heat in a water bath at 40°C with stirring for 10 min, and then ultrasonically adsorb for 6 min. After adsorption, the suspension is filtered, washed with deionized water three times, and dried in an oven at 60°C for 24 h to obtain a solid precursor;
[0071] (4) The solid precursor obtained in step (3) was placed in a tube furnace, heated to 500° C. at 2° C. / min under an argon atmosphere, kept at this temperature for 2 h, and then naturally cooled to obtain a black solid powder.
[0072] (5) The black solid powder obtained in step (4) is placed in a tubular furnace, heated to 350°C at 10°C / min and kept warm for 5 hours under an oxygen atmosphere, and then heated to 650°C at 10°C / min and kept warm for 15 hours to obtain a nickel-rich positive electrode material with a three-shell structure having a nickel concentration gradient, wherein the outermost shell has a diameter of about 800 nm.
[0073] Transmission electron microscopy photos of nickel-rich cathode materials with a three-shell structure with nickel concentration gradient Figure 1 As shown, the transmission electron microscopy photos after embedding the slices are as follows Figure 2 shown. Figure 3 The figure shows the transmission electron microscopy-energy dispersive X-ray spectroscopy elemental analysis of the obtained nickel-rich positive electrode material with a three-shell structure with a nickel concentration gradient after embedding and slicing. It can be seen from the figure that the Ni element on the inner and outer shells presents a gradient distribution, which is specifically manifested in that the Ni content in the inner shell is high and the Ni content in the outer shell is relatively low. Figure 4 This is an X-ray diffraction diagram of a nickel-rich cathode material with a three-shell structure and a nickel concentration gradient. It can be seen that the synthesized material belongs to a cubic phase, R-3m space group, and has a layered structure of α-NaFeO4. The two characteristic peaks with the strongest peak intensity correspond to the (003) and (104) crystal planes, respectively. The characteristic peaks of the sample are very sharp, indicating that the material has good crystallinity. There are no impurity peaks in the X-ray diffraction spectrum, indicating that the sample is a pure phase material, and all satisfy I(003) / I(102)≥1.2, indicating that the degree of cation mixing in the material is low. Figure 5 As shown, the surface of the nickel-rich positive electrode material with a three-shell structure having a nickel concentration gradient has Ni elements of +2 and +3 valences, Co of +4 valences, and Mn of +4 valences. Figure 6 As shown in the figure, when the above nickel-rich cathode material with a nickel concentration gradient three-shell structure is used as a lithium-ion battery cathode material, it can be stably cycled for more than 100 cycles at a rate of 0.3C in the voltage range of 2.5-4.3V, and the specific capacity can still be maintained at more than 190mAh / g, which is far superior to the nickel-rich cathode material nanoparticles of the same composition. Figure 7 As shown, the exothermic peak temperature of the nickel-rich positive electrode material with a three-shell structure having a nickel concentration gradient appears at 272.9°C, which is higher than the exothermic peak temperature of the nickel-rich positive electrode material nanoparticles of 241.1°C, indicating that the nickel-rich positive electrode material with a three-shell structure having a nickel concentration gradient has excellent thermal stability.
[0074] Example 2
[0075] A method for preparing a hollow multi-shell structure material having a metal element concentration gradient, the method comprising:
[0076] (1) A 2.5 M sucrose aqueous solution was placed in a reactor at 180° C. for hydrothermal reaction for 150 min. After natural cooling, it was filtered and washed with water 3 times and ethanol 3 times. The product was placed in an oven at 60° C. and dried for 24 h to obtain a carbon sphere template with a diameter of 2.7 μm.
[0077] (2) Grind 1 g of the carbon sphere template obtained in step (1) and add it to a metal salt solution in a molar ratio of 100:10:1:1, i.e., 1 M lithium acetate solution, 0.1 M nickel acetate solution, 0.01 M manganese acetate solution and 0.01 M cobalt acetate, and the solvent is a mixture of 30 ml of deionized water and 20 ml of anhydrous ethanol, stir for 10 min, and then ultrasonicate for 10 min. After the ultrasonication is completed, stir and adsorb at 40° C. for 12 h;
[0078] (3) Add 0.04M cobalt acetate and 0.16M manganese acetate to the solution obtained in (2), heat in a water bath at 40°C with stirring for 10 min, and then ultrasonically adsorb for 6 min. After adsorption, the suspension is filtered, washed with deionized water three times, and dried in an oven at 60°C for 24 h to obtain a solid precursor;
[0079] (4) The solid precursor obtained in step (3) was placed in a tube furnace, heated to 500° C. at 2° C. / min under an argon atmosphere, kept at this temperature for 2 h, and then naturally cooled to obtain a black solid powder.
[0080] (5) The black solid precursor obtained in step (4) is placed in a tubular furnace, heated to 400°C at 5°C / min and kept warm for 5 hours under an oxygen atmosphere, and then heated to 650°C at 5°C / min and kept warm for 15 hours to obtain a nickel-rich positive electrode material with a two-shell structure having a nickel concentration gradient, and the outermost shell diameter is about 750nm.
[0081] like Figure 6 As shown, when the above-mentioned nickel-rich positive electrode material with a two-shell structure having a nickel concentration gradient is used as a positive electrode material for a lithium-ion battery, it can maintain a specific capacity of more than 180 mAh / g after stably cycling for more than 100 cycles at a rate of 0.3C in the voltage range of 2.5-4.3 V, and its performance far exceeds that of nickel-rich positive electrode material nanoparticles with the same composition.
[0082] Example 3
[0083] A method for preparing a hollow multi-shell structure material having a metal element concentration gradient, the method comprising:
[0084] (1) A 3M sucrose aqueous solution was placed in a reactor at 210°C for hydrothermal reaction for 120 min, and then naturally cooled and filtered. The product was washed with water for 3 times and ethanol for 3 times, and then dried in an oven at 60°C for 24 h to obtain a carbon sphere template with a diameter of 3.0 μm.
[0085] (2) Grind 1 g of the carbon sphere template obtained in step (1) and add it to a metal salt solution containing 5 M lithium nitrate solution, 0.5 M nickel nitrate solution, 0.05 M manganese nitrate solution and 0.05 M cobalt nitrate, and the solvent is a mixture of 30 ml deionized water and 20 ml anhydrous ethanol, stir for 10 min, and then ultrasonicate for 10 min. After the ultrasonication is completed, stir and adsorb at 20° C. for 12 h;
[0086] (3) Add 5M lithium nitrate solution to the solution obtained in (2), stir at 20°C for 10 min, then ultrasonicate for 10 min, and then adsorb for 2 h. After adsorption, filter the suspension, wash it with deionized water and ethanol alternately for 3 times, and dry it in an oven at 80°C for 24 h to obtain a solid precursor;
[0087] (4) The solid precursor obtained in step (3) was placed in a tube furnace, heated to 200° C. at 0.5° C. / min under a nitrogen atmosphere, kept at this temperature for 10 h, and then naturally cooled to obtain a black solid powder.
[0088] (5) The black solid precursor obtained in step (4) is placed in a tubular furnace, and the temperature is increased to 350°C at 0.5°C / min and kept at this temperature for 5 hours under air atmosphere, and then the temperature is increased to 650°C at 5°C / min and kept at this temperature for 15 hours to obtain a nickel-rich positive electrode material with a three-shell structure having a lithium concentration gradient, and the outermost shell has a diameter of about 850 nm.
[0089] Example 4
[0090] A method for preparing a multi-shell structure material having a metal element concentration gradient, the method comprising:
[0091] (1) A 2M sucrose aqueous solution was placed in a reactor at 160°C for hydrothermal reaction for 200 min, and then naturally cooled and filtered. The mixture was washed with water for 3 times and ethanol for 3 times. The product was dried in an oven at 60°C for 24 h to obtain a carbon sphere template with a diameter of 2.6 μm.
[0092] (2) Grind 1 g of the carbon sphere template obtained in step (1) and add it to a metal salt solution containing 1 M lithium sulfate solution, 0.1 M cobalt sulfate solution, and a solvent of a mixture of 30 ml deionized water and 20 ml anhydrous ethanol, stir for 10 min, and then ultrasonicate for 10 min. After the ultrasonication is completed, stir and adsorb at 40° C. for 12 h;
[0093] (3) Add 0.16M nickel sulfate and 0.16M manganese sulfate to the solution obtained in (2), heat in a water bath at 40°C with stirring for 10 minutes, and then ultrasonically adsorb for 10 minutes. After adsorption, the suspension is filtered, washed with deionized water three times, and dried in an oven at 100°C for 24 hours to obtain a solid precursor;
[0094] (4) The solid powder obtained in (3) was redispersed in 0.16M nickel sulfate and 0.16M manganese sulfate solution, heated in a water bath at 40°C with stirring for 10 minutes, and then ultrasonically adsorbed for 10 minutes. After the adsorption was completed, the suspension was filtered, washed with deionized water three times, and dried in an oven at 100°C for 24 hours to obtain a solid precursor;
[0095] (5) The solid precursor obtained in step (4) was placed in a tube furnace, heated to 800° C. at 20° C. / min under an argon atmosphere, kept at that temperature for 2 h, and then naturally cooled to obtain a black solid powder.
[0096] (6) The black solid precursor obtained in step (4) is placed in a tubular furnace, in a mixed atmosphere of oxygen and nitrogen with an oxygen volume fraction of 80%, the temperature is increased to 300°C at 0.5°C / min and kept warm for 10 hours, and then the temperature is increased to 1000°C at 20°C / min and kept warm for 15 hours to obtain a cobalt-rich positive electrode material with a two-shell structure having a cobalt concentration gradient, and the outermost shell has a diameter of about 700 nm.
[0097] Example 5
[0098] A method for preparing a multi-shell structure material having a metal element concentration gradient, the method comprising:
[0099] (1) A 1.5 M sucrose aqueous solution was placed in a reactor at 200° C. for hydrothermal reaction for 135 min. After natural cooling, the mixture was filtered and washed with water 3 times and ethanol 3 times. The product was placed in an oven at 60° C. and dried for 24 h to obtain a carbon sphere template with a diameter of 2.9 μm.
[0100] (2) Grind 1 g of the carbon sphere template obtained in step (1) and add it to a metal salt solution containing 1 M lithium chloride solution, 1.0 M manganese chloride solution, 0.1 M nickel chloride solution and 0.1 M cobalt chloride, and the solvent is a mixture of 30 ml deionized water and 20 ml anhydrous ethanol, stir for 10 min, and then ultrasonicate for 10 min. After the ultrasonication is completed, stir and adsorb at 60° C. for 1 h;
[0101] (3) Add 0.01M nickel chloride and 0.01M cobalt chloride to the solution obtained in (2), respectively, and heat in a water bath at 60°C with stirring for 6 minutes. After adsorption is completed, the suspension is filtered, washed twice with deionized water and methanol alternately, and dried in an oven at 100°C for 24 hours to obtain a solid precursor;
[0102] (4) The solid powder obtained in (3) was redispersed in 0.01M nickel chloride and 0.01M cobalt chloride solution, heated in a water bath at 60°C with stirring for 6 min. After adsorption, the suspension was filtered, washed twice with deionized water and methanol alternately, and dried in an oven at 100°C for 24 h to obtain a solid precursor;
[0103] (5) The solid powder obtained in (4) was redispersed in 0.01M nickel chloride and 0.01M cobalt chloride solution, heated in a water bath at 60°C with stirring for 6 min. After adsorption, the suspension was filtered, washed twice with deionized water and methanol alternately, and dried in an oven at 100°C for 24 h to obtain a solid precursor;
[0104] (6) The solid precursor obtained in step (5) was placed in a tube furnace, heated to 400° C. at 2° C. / min under an argon atmosphere, kept at that temperature for 5 h, and then naturally cooled to obtain a black solid powder.
[0105] (7) The black solid precursor obtained in step (6) is placed in a tubular furnace, heated to 350° C. at 5° C. / min and kept warm for 5 h under an oxygen atmosphere, and then heated to 500° C. at 5° C. / min and kept warm for 30 h to obtain a manganese-rich positive electrode material with a two-shell structure having a manganese concentration gradient, and the outermost shell diameter is about 800 nm.
[0106] Example 6
[0107] A method for preparing a multi-shell structure material having a metal element concentration gradient, the method comprising:
[0108] (1) A 1.5 M sucrose aqueous solution was placed in a reactor at 190° C. for hydrothermal reaction for 140 min. After natural cooling, the mixture was filtered and washed with water 3 times and ethanol 3 times. The product was placed in an oven at 60° C. and dried for 24 h to obtain a carbon sphere template with a diameter of 2.8 μm.
[0109] (2) Grind 1 g of the carbon sphere template obtained in step (1) and add it to a metal salt solution containing 4 M lithium nitrate solution, 0.4 M nickel nitrate solution, 0.04 M manganese acetate solution and 0.04 M cobalt acetate, and the solvent is a mixture of 30 ml deionized water and 20 ml anhydrous ethanol, stir for 10 min, and then ultrasonicate for 10 min. After the ultrasonication is completed, stir and adsorb at 40° C. for 48 h;
[0110] (3) Add 0.04M cobalt acetate and 0.04M manganese acetate to the solution obtained in (2), heat in a water bath at 40°C with stirring for 10 min, and then ultrasonically adsorb for 10 min. After adsorption, the suspension is filtered, washed with deionized water three times, and dried in an oven at 60°C for 24 h to obtain a solid precursor;
[0111] (4) The solid precursor obtained in step (3) was placed in a tube furnace, heated to 500° C. at 2° C. / min under an argon atmosphere, kept at this temperature for 2 h, and then naturally cooled to obtain a black solid powder.
[0112] (5) The black solid precursor obtained in step (4) is placed in a tubular furnace, and in a mixed atmosphere of nitrogen and oxygen with an oxygen volume fraction of 10%, the temperature is raised to 500°C at 10°C / min and kept warm for 1 hour, and then the temperature is raised to 1000°C at 10°C / min and kept warm for 15 hours to obtain a nickel-rich positive electrode material with a two-shell structure having a nickel concentration gradient, and the outermost shell layer has a diameter of about 850nm.
[0113] Example 7
[0114] A method for preparing a multi-shell structure material having a metal element concentration gradient, the method comprising:
[0115] (1) A 1.5 M sucrose aqueous solution was placed in a reactor at 190° C. for hydrothermal reaction for 140 min. After natural cooling, the mixture was filtered and washed with water 3 times and ethanol 3 times. The product was placed in an oven at 60° C. and dried for 24 h to obtain a carbon sphere template with a diameter of 2.8 μm.
[0116] (2) Grind 1 g of the carbon sphere template obtained in step (1) and add it to a nickel acetate solution with a nickel acetate concentration of 0.3 M and a solvent of a mixture of 30 ml of deionized water and 20 ml of anhydrous ethanol, stir for 10 min, and then ultrasonicate for 10 min. After the ultrasonication is completed, stir and adsorb at 40° C. for 48 h;
[0117] (3) Add 0.01M cobalt acetate to the solution obtained in (2), heat in a water bath at 40°C with stirring for 10 min, and then ultrasonically adsorb for 10 min. After adsorption is completed, the suspension is filtered, washed with deionized water three times, and dried in an oven at 60°C for 24 h to obtain a solid precursor;
[0118] (4) The solid precursor obtained in step (3) was placed in a tube furnace, heated to 500° C. at 2° C. / min under an argon atmosphere, kept at this temperature for 2 h, and then naturally cooled to obtain a black solid powder.
[0119] (5) The black solid precursor obtained in step (4) is placed in a tubular furnace, in a mixed atmosphere of nitrogen and oxygen with an oxygen volume fraction of 25%, the temperature is raised to 350°C at 5°C / min and kept warm for 5 hours, and then the temperature is raised to 600°C at 10°C / min and kept warm for 15 hours to obtain a nickel-cobalt oxide material with a three-shell structure having a nickel concentration gradient, and the outermost shell has a diameter of about 900 nm.
[0120] Example 8
[0121] A method for preparing a multi-shell structure nickel-rich positive electrode material, the method comprising:
[0122] (1) A 1.5 M sucrose aqueous solution was placed in a reactor at 190° C. for hydrothermal reaction for 140 min. After natural cooling, the mixture was filtered and washed with water 3 times and ethanol 3 times. The product was placed in an oven at 60° C. and dried for 24 h to obtain a carbon sphere template with a diameter of 2.8 μm.
[0123] (2) Grind 1 g of the carbon sphere template obtained in step (1) and add it to a metal salt solution in a molar ratio of 100:10:1:1, i.e., 2 M lithium acetate solution, 0.2 M nickel acetate solution, 0.02 M manganese acetate solution and 0.02 M cobalt acetate, and the solvent is a mixture of 30 ml of deionized water and 20 ml of anhydrous ethanol, stir for 10 min, and then ultrasonicate for 10 min. After the ultrasonication is completed, stir and adsorb at 40° C. for 48 h;
[0124] (3) The solid precursor obtained in step (2) is placed in a tubular furnace, and the temperature is increased to 500°C at 2°C / min under an argon atmosphere, and kept warm for 2 hours. Then, the temperature is increased to 350°C at 10°C / min under an oxygen atmosphere and kept warm for 5 hours, and then the temperature is increased to 650°C at 10°C / min and kept warm for 15 hours to obtain a three-shell nickel-rich positive electrode material, and the outermost shell has a diameter of about 800 nm.
[0125] The present invention is based on the sequential template method and adopts a secondary adsorption strategy combined with a secondary calcination treatment. The secondary adsorption can regulate the gradient distribution of the metal ion precursor in the template. The secondary calcination treatment, that is, first calcining in an inert atmosphere to fix the position of the metal ions, and then calcining in an oxidizing atmosphere to remove the template, thereby synthesizing a multi-shell structure material with a metal element concentration gradient, and regulating the concentration of the metal ion precursor in the solution, the adsorption order, the adsorption time, the calcination temperature and the calcination time and other conditions, thereby accurately controlling the number of shells and effectively controlling the gradient distribution of the metal element concentration in the shells.
[0126] Any contents not described in detail in the present invention can be based on the conventional technical knowledge in the art.
[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that any modification or equivalent replacement of the technical solutions of the present invention does not depart from the spirit and scope of the technical solutions of the present invention and should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a hollow multi-shell structure material having a metal element concentration gradient, comprising the following steps: 1) A carbon source aqueous solution is subjected to a hydrothermal reaction, and then filtered, washed, and dried to obtain a micro-nano-sized colloidal carbon sphere template; 2) dispersing the carbon sphere template obtained in step 1) in a metal salt solution to obtain a suspension, stirring, heat preservation and adsorption to obtain a suspension; 3) adding metal salt to the suspension obtained in step 2) again, performing secondary adsorption, filtering and drying to obtain a solid precursor after secondary adsorption; 4) calcining the solid precursor obtained in step 3) at high temperature under an inert atmosphere to obtain a solid powder; 5) The solid powder obtained in step 4) is calcined at a high temperature in an oxygen or air atmosphere to obtain a hollow multi-shell structure material with a metal element concentration gradient.
2. The preparation method according to claim 1, characterized in that: The colloidal carbon spheres in step 1) are obtained by hydrothermal reaction.
3. The preparation method according to claim 1, characterized in that: The solvent of the metal salt solution in step 2) is one or more of water, acetone and ethanol; The metal salt includes one or more of lithium chloride, nickel chloride, manganese chloride, cobalt chloride, lithium acetate, lithium acetate dihydrate, nickel acetate, nickel acetate tetrahydrate, manganese acetate tetrahydrate, cobalt acetate, cobalt acetate tetrahydrate, lithium sulfate, lithium sulfate dihydrate, nickel sulfate, nickel sulfate tetrahydrate, manganese sulfate, manganese sulfate tetrahydrate, cobalt sulfate, cobalt sulfate tetrahydrate, lithium nitrate, lithium nitrate dihydrate, nickel nitrate, nickel nitrate tetrahydrate, manganese nitrate, manganese nitrate tetrahydrate, cobalt nitrate, and cobalt nitrate tetrahydrate; The concentration of the metal salt solution is 0.01-5M; In the step 2), the adsorption temperature is 20-60° C. and the adsorption time is 1-48 h.
4. The preparation method according to claim 1, characterized in that: The solvent of the metal salt solution in step 3) is one or more of water, acetone and ethanol; The metal salt includes one or more of lithium chloride, nickel chloride, manganese chloride, cobalt chloride, lithium acetate, lithium acetate dihydrate, nickel acetate, nickel acetate tetrahydrate, manganese acetate tetrahydrate, cobalt acetate, cobalt acetate tetrahydrate, lithium sulfate, lithium sulfate dihydrate, nickel sulfate, nickel sulfate tetrahydrate, manganese sulfate, manganese sulfate tetrahydrate, cobalt sulfate, cobalt sulfate tetrahydrate, lithium nitrate, lithium nitrate dihydrate, nickel nitrate, nickel nitrate tetrahydrate, manganese nitrate, manganese nitrate tetrahydrate, cobalt nitrate, and cobalt nitrate tetrahydrate; The concentration of the metal salt solution is 0.01-5M; In the step 3), the adsorption temperature is 20-60°C; the adsorption time is 0.1-2h; the drying temperature is 60-100°C; and the drying time is 6-24h; The adsorption, filtration and drying process in step 3) can be repeated multiple times to obtain a solid precursor after multiple adsorptions.
5. The preparation method according to claim 1, characterized in that: In the step 4), the calcination temperature is 200-800° C., the calcination time is 0.5-10 h, and the calcination heating rate is 0.5-20° C. / min; the calcination atmosphere is one of argon or nitrogen.
6. The preparation method according to claim 1, characterized in that: The roasting in step 5) comprises a two-step roasting process; The first step is a calcination temperature of 300-500°C, a calcination time of 1-10h, and a calcination heating rate of 0.5-10°C / min; The second step is calcination temperature of 500-1000℃, calcination time of 15-30h, and calcination heating rate of 0.5-20℃ / min; The calcining atmosphere is one of air, oxygen, or a mixture of oxygen and nitrogen, wherein the proportion of oxygen in the mixture of oxygen and nitrogen is 10%-100%.
7. A hollow multi-shell structure material having a metal element concentration gradient, characterized in that: The hollow multi-shell structure material with a metal element concentration gradient is obtained by the preparation method described in any one of claims 1-6.
8. The hollow multi-shell structure material with a metal element concentration gradient according to claim 7, characterized in that: The metal element concentration gradient means that the concentration of one metal element on different shells from the inside to the outside is distributed from high to low, and correspondingly, the concentration of other metal elements is distributed from low to high; The metal elements with concentration gradient include one or more of lithium, nickel, cobalt and manganese; The hollow multi-shell structure material comprises at least one cavity and at least two layers of shell walls.
9. Application of the multi-shell structure material with metal element concentration gradient according to claim 7 or 8 in energy storage.
Citation Information
Patent Citations
Multi-shell-layer metal oxide hollow ball and preparation method thereof
CN102464304A
Preparation method and application of amorphous metal oxide hollow multi-shell material
CN113149077A
Nanoparticle-encapsulated multi-core multi-shell hollow material as well as preparation method and application thereof
CN113363434A
Amorphous carbon composite metal oxide Yolk-Shell material and preparation method and application thereof
CN115140727A
Preparation method and application of amorphous metal oxide hollow multi-shell material
US20240140818A1